2020
DOI: 10.1186/s12933-020-01045-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,5-anhydroglucitol levels on culprit plaque rupture in diabetic patients with acute coronary syndrome

Abstract: Background: Postprandial hyperglycemia was reported to play a key role in established risk factors of coronary artery diseases (CAD) and cardiovascular events. Serum 1,5-anhydroglucitol (1,5-AG) levels are known to be a clinical marker of short-term postprandial glucose (PPG) excursions. Low serum 1,5-AG levels have been associated with occurrence of CAD. However, the relationship between 1,5-AG levels and coronary plaque rupture has not been fully elucidated. The aim of this study was to evaluate 1,5-AG as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…During the follow-up period in the present study, serum 1,5-AG levels were associated with adverse clinical events, including all-cause death, CV death, and TVR. In addition to the recent report that 1,5-AG may be related to plaque rupture in diabetic patients with ACS ( 48 ), we hypothesized that the relationship between 1,5-AG and CAC in our study may be another important contributing factor supporting the hypothesis that low serum 1,5-AG levels could predict adverse outcomes. Interestingly, recent studies have reported that an intensive glucose-lowering intervention may increase serum 1,5-AG levels ( 49 ) and attenuate the progression of CAC in patients with DM ( 50 ).…”
Section: Discussionsupporting
confidence: 64%
“…During the follow-up period in the present study, serum 1,5-AG levels were associated with adverse clinical events, including all-cause death, CV death, and TVR. In addition to the recent report that 1,5-AG may be related to plaque rupture in diabetic patients with ACS ( 48 ), we hypothesized that the relationship between 1,5-AG and CAC in our study may be another important contributing factor supporting the hypothesis that low serum 1,5-AG levels could predict adverse outcomes. Interestingly, recent studies have reported that an intensive glucose-lowering intervention may increase serum 1,5-AG levels ( 49 ) and attenuate the progression of CAC in patients with DM ( 50 ).…”
Section: Discussionsupporting
confidence: 64%
“…Blood 1,5-AHG quantification of at-risk individuals could provide a targeted screening strategy to prevent the development of T2DM or identify those with asymptomatic diabetes [102]. The glycemic biomarker 1,5-AHG not only has a diagnostic application for diabetes, but it has the potential to evaluate the risk of long-term complications, including the most documented association with cardiovascular diseases and mortality in people with T2DM [96,102,103]. There is also evidence of its prognostic value for microvascular complications such as retinopathy and CKD [97].…”
Section: 5-anhydroglucitolmentioning
confidence: 99%
“…It is worth noting that, in this study, coronary atheroma volume and plaque burden were not significantly associated with serum levels of 1,5-AG [ 37 ]. A recent study conducted by Su et al confirmed that 1,5-AG serum levels are associated with high risk of coronary plaque rupture in diabetic patients with ACS, which correlates with postprandial glycemia and is related to the pathogenesis of plaque rupture in diabetes [ 38 ].…”
Section: Resultsmentioning
confidence: 99%